V.V. Davydov: On the Scale of Historical Reason - Lobastov G.V (Moscow State University of Psychology and Education, 2020)
The paper attempts to take a look at the works of V.V. Davydov from the perspective of classical historical ideas of objective forms of thinking, through the prism of dialectics as logics - in other words, through the notions that Davydov himself considered as basic foundations of his pedagogical transformations. Appreciation or rejection of Davydov's achievements depends entirely on the position of 'experts': looking at his accomplishments with the eyes of Hegel or Marx, or analyzing them from the point of view of real educational practice are two principally different things. The extent to which historical classics of philosophy and pedagogy revealed itself in Davydov's activity and how it was or was not implemented - these are the issues that await their exploration. The paper outlines some topics for such research.